The prospect of using borehole water for space cooling in ghana: A numerical study - Ibrahim Abu Alhassan; Samuel Boahen; Kofi Owura Amoabeng; Richard Opoku; Peter Oppong Tawiah; Bismark Baah (Scientific African)
Residential facilities in hot climates, like Ghana, account for significant cooling demands that are driven by high cooling loads due to high ambient temperatures. This study explores the potential of utilizing borehole water cooling systems as an alternative to conventional air-cooled air conditioning systems for space cooling in Ghana. The study compares the performance characteristics, annual energy consumption, and CO2 emissions of the borehole water cooling system (BWCS) to those of the conventional air-cooled air conditioning systems (AACS) at varying outdoor air temperatures using a numerical approach. The BWCS showed higher cooling capacity, lower compressor power consumption, and higher COP with the potential to save up to 19.5 % of the annual energy consumed by the AACS. The BWCS also showed significant reductions in CO2 emissions to underscore the potential of borehole water cooling systems as a sustainable alternative to conventional air conditioning systems in hot climate regions like Ghana. By leveraging the stable temperature of groundwater, the BWCS can significantly enhance energy efficiency, reduce CO2 emissions, and contribute to environmental sustainability.